2019
DOI: 10.1002/gsj.1355
|View full text |Cite
|
Sign up to set email alerts
|

Signaling legitimacy across institutional contexts—The intermediary role of corporate social responsibility rating agencies

Abstract: Research Summary Good corporate social responsibility (CSR) ratings can increase a firm's legitimacy and reduce its default risk. Yet, the interpretation of CSR varies between different countries. We investigate whether CSR ratings have a risk‐mitigating effect across different institutional contexts. We find that good CSR ratings have a general risk‐mitigating effect. Yet, we also find that the effect decreases when the rating agency is embedded in the institutional context of its home country and the rated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 77 publications
(151 reference statements)
0
22
0
Order By: Relevance
“…Davies and Crane [24] defined ethical, legal, and economic factors as the main priorities of any CSR activity. Dahlsrud [25] identified that there are five key dimensions of CSR, including environmental, social, economic, stakeholder, and voluntary action dimensions. The five-factor CSR model presented by Dahlsrud [25] corresponds to the standard CSR model of Carroll [2], in which economic, legal, and ethical domains are the same as those identified by Dahlsrud [25], and environment may fall under legal if it is obligatory by state laws or voluntary if state laws do not restrict it.…”
Section: Methodsmentioning
confidence: 99%
“…Davies and Crane [24] defined ethical, legal, and economic factors as the main priorities of any CSR activity. Dahlsrud [25] identified that there are five key dimensions of CSR, including environmental, social, economic, stakeholder, and voluntary action dimensions. The five-factor CSR model presented by Dahlsrud [25] corresponds to the standard CSR model of Carroll [2], in which economic, legal, and ethical domains are the same as those identified by Dahlsrud [25], and environment may fall under legal if it is obligatory by state laws or voluntary if state laws do not restrict it.…”
Section: Methodsmentioning
confidence: 99%
“…Other stakeholders may also exert substantial pressure toward CSP. Debtholders may be instrumentally attracted by the risk reducing capacity of CSP (Kölbel & Busch, 2019; Shiu & Yang, 2017), but may oppose initiatives that redistribute firm value. Employees and customers may demand CSP based mostly on relational and moral motives (Aguilera et al, 2007), while strategic partners, such as suppliers, are more concerned with firm survival (instrumental) and relational stakeholder management.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…First, we add to the global strategy and CSR literatures by identifying and modeling how international trade and investment agreements, through policy transferal, encourage the adoption and upward harmonization of CSR standards by firms. Scholars have suggested that CSR is a “cross-sectional” phenomenon that requires concurrent examination of why firms engage in CSR and why countries and global stakeholders promote it (Bitektine, 2011 ; Kölbel & Busch, 2019 ; Sahlin-Andersson, 2006 ). This literature focuses on the importance of global civil society and private regulatory frameworks such as those established by the United Nations and other intergovernmental organizations (Sahlin-Andersson, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if a state joins an agreement that contains specific labor standards, those standards are typically then reflected in domestic law or regulation, and therefore firms within that state will have to adhere to these now harmonized standards. These enforcement mechanisms are coercive in the sense that they are reflected in laws and rules established by member states, but also support the development of a shared understanding about what is acceptable or legitimate both between and within states (Bitektine, 2011 ; Kölbel & Busch, 2019 ).…”
Section: Global Integration and The Adoption Of Csr Standards: A Polimentioning
confidence: 99%